Characteristics of specific training in elite handball players specialized in goalkeeper position - Mihaila, I.; Popescu, M.-C.; Pascual-Fuertes, X.; Popescu, D.-C.; Stancu, M.; Acsinte, A.; Ciorba, C. (Pedagogy of Physical Culture and Sports, 2024)
Background and Study Aim. Elite handball goalkeepers undergo intensive training for reflexes and advanced techniques. They develop mental toughness to handle the pressure and responsibility at key moments of the game. Thus, they protect the goal of the team. This study aims to investigate and highlight the specific training characteristics of elite handball players specialized in the goalkeeper position.